Circulating Microparticles Are Elevated in Treated HIV‐1 Infection and Are Deleterious to Endothelial Cell Function. Issue 4 (19th February 2019) - Hijmans, Jamie G.; Stockelman, Kelly A.; Garcia, Vinicius; Levy, Ma'ayan V.; Brewster, L. Madden; Bammert, Tyler D.; Greiner, Jared J.; Stauffer, Brian L.; Connick, Elizabeth; DeSouza, Christopher A.
Abstract : Background: Circulating microparticles have emerged as biomarkers and effectors of vascular disease. Elevated rates of cardiovascular disease are seen in HIV‐1–seropositive individuals. The aims of this study were to determine: (1) if circulating microparticles are elevated in antiretroviral therapy–treated HIV‐1–seropositive adults; and (2) the effects of microparticles isolated from antiretroviral therapy–treated HIV‐1–seropositive adults on endothelial cell function, in vitro. Methods and Results: Circulating levels of endothelial‐, platelet‐, monocyte‐, and leukocyte‐derived microparticles were determined by flow cytometry in plasma from 15 healthy and 15 antiretroviral therapy–treated, virologically suppressed HIV‐1–seropositive men. Human umbilical vein endothelial cells were treated with microparticles from individual subjects for 24 hours; thereafter, endothelial cell inflammation, oxidative stress, senescence, and apoptosis were assessed. Circulating concentrations of endothelial‐, platelet‐, monocyte‐, and leukocyte‐derived microparticles were significantly higher (≈35%–225%) in the HIV‐1–seropositive compared with healthy men. Microparticles from HIV‐1–seropositive men induced significantly greater endothelial cell release of interleukin‐6 and interleukin‐8 (≈20% and ≈35%, respectively) and nuclear factor‐κB expression while suppressing anti‐inflammatory microRNAs (miR‐146a and miR‐181b). Intracellular reactive oxygen species production and expression of reactive oxygen species–related heat shock protein 70 were both higher in cells treated with microparticles from the HIV‐1–seropositive men. In addition, the percentage of senescent cells was significantly higher and sirtuin 1 expression lower in cells treated with HIV‐1–related microparticles. Finally, caspase‐3 was significantly elevated by microparticles from HIV‐1–seropositive men. Conclusions: Circulating concentrations of endothelial‐, platelet‐, monocyte‐, and leukocyte‐derived microparticles were higher in antiretroviral therapy–treated HIV‐1–seropositive men and adversely affect endothelial cells promoting cellular inflammation, oxidative stress, senescence, and apoptosis. Circulating microparticles may contribute to the vascular risk associated with HIV‐1 infection.